Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the inverse of the function \( y = 2x^2 - 4 \), follow these steps:
1. Start with the given function:
[tex]\[ y = 2x^2 - 4 \][/tex]
2. Swap \(y\) and \(x\): To find the inverse, we interchange the roles of \(x\) and \(y\).
[tex]\[ x = 2y^2 - 4 \][/tex]
3. Solve for \(y\): We need to isolate \(y\) in terms of \(x\).
- First, add 4 to both sides to start isolating \(y^2\):
[tex]\[ x + 4 = 2y^2 \][/tex]
- Next, divide both sides by 2 to further isolate \(y^2\):
[tex]\[ \frac{x + 4}{2} = y^2 \][/tex]
- Finally, take the square root of both sides to solve for \(y\):
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
4. State the inverse functions:
The resulting expressions represent the inverse functions of the given original function. Therefore, we have:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
And equivalently, since taking the square root of a fraction is the same as taking the square root of the numerator and denominator separately:
[tex]\[ y = \pm \frac{\sqrt{x + 4}}{2} \][/tex]
Thus, the inverse functions of the original function \( y = 2x^2 - 4 \) are:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
or equivalently:
[tex]\[ y = \pm \frac{\sqrt{x + 4}}{2} \][/tex]
So, the correct answer is:
[tex]\[ y = \pm \sqrt{\frac{x+4}{2}} \][/tex]
or
[tex]\[ y = \pm \frac{\sqrt{x+4}}{2} \][/tex]
1. Start with the given function:
[tex]\[ y = 2x^2 - 4 \][/tex]
2. Swap \(y\) and \(x\): To find the inverse, we interchange the roles of \(x\) and \(y\).
[tex]\[ x = 2y^2 - 4 \][/tex]
3. Solve for \(y\): We need to isolate \(y\) in terms of \(x\).
- First, add 4 to both sides to start isolating \(y^2\):
[tex]\[ x + 4 = 2y^2 \][/tex]
- Next, divide both sides by 2 to further isolate \(y^2\):
[tex]\[ \frac{x + 4}{2} = y^2 \][/tex]
- Finally, take the square root of both sides to solve for \(y\):
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
4. State the inverse functions:
The resulting expressions represent the inverse functions of the given original function. Therefore, we have:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
And equivalently, since taking the square root of a fraction is the same as taking the square root of the numerator and denominator separately:
[tex]\[ y = \pm \frac{\sqrt{x + 4}}{2} \][/tex]
Thus, the inverse functions of the original function \( y = 2x^2 - 4 \) are:
[tex]\[ y = \pm \sqrt{\frac{x + 4}{2}} \][/tex]
or equivalently:
[tex]\[ y = \pm \frac{\sqrt{x + 4}}{2} \][/tex]
So, the correct answer is:
[tex]\[ y = \pm \sqrt{\frac{x+4}{2}} \][/tex]
or
[tex]\[ y = \pm \frac{\sqrt{x+4}}{2} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.